Health problems in top-level female football players: a four-season prospective study in the Finnish top football league - Mustakoski, I.; Kurittu, E.; Vasankari, T.; Brinck, T.; Parkkari, J.; Heinonen, O.; Leppänen, M. (Science and Medicine in Football, 2025)
The objective was to examine the prevalence, incidence rate, and burden of health problems among top-level female football players in Finland. During the four-season follow-up, altogether 372 players (mean age 20.6 years) from 13 teams participated. Players reported all health problems (sudden-onset injuries, gradual-onset injuries and illnesses) weekly using a mobile application. Training exposure was collected at the team level from coaches and individual match exposure from the match statistics. Prevalence, incidence rate, and burden of injuries and illnesses were calculated. The average weekly response rate was 87%. The weekly prevalence of any health problem was 23.1% (95% CI 21.0-25.3%). Prevalence of health problems causing moderate or severe modifications in sports participation/performance (substantial health problems) was 15.8% (95% CI 14.2-17.7%). Altogether 783 injuries (5.5 injuries per 1000 hours) and 586 illnesses (1.7 cases per 365 player-days) were reported. Seventy percent of injuries were sudden-onset (3.7 per 1000 hours) and 30% gradual-onset injuries (1.6 per 1000 hours). The incidence rate of sudden-onset injuries per 1000 hours was 2.3 (1.9-2.7) in training and 15.3 (11.2-21.0) in match play. Sudden-onset injuries accounted for 54% of total time loss, gradual-onset injuries 17%, and illnesses 30%. Thigh (19%) and ankle (18%) injuries were most common. Knee injuries, particularly ACL injuries, were the most severe, with knee injuries causing 53% and ACL injuries 28% of all injury time loss. Sudden-onset injuries, occurring mainly in matches, posed the greatest health burden for female football players.